EFEKTIVITAS PEMANFAATAN DANA KREDIT USAHA RAKYAT (KUR) DALAM MENGEMBANGKAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA TAMBOLI KECAMATAN SAMATURU - Mirnawati Mirnawati; Amir Sahaka; Muhammad Akbar (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The People's Business Credit (KUR) is a government program launched in November 2007 by President Susilo Bambang Yodoyono, which is given to micro-entrepreneurs who are feasible but not yet bankable. One of the efforts that can be made to empower a productive economy in order to reduce unemployment is to help open employment / business for those who need work, namely entrepreneurship by fostering Micro, Small and Medium Enterprises (MSMEs). However, the provision of People's Business Credit (KUR) funds in Tamboli Village, Samaturu District was not fully used in accordance with the initial loan agreement.The formulation of the problem in this study is How to use the People's Business Credit (KUR) fund in developing Micro, Small and Medium Enterprises (MSMEs) in Tamboli Village, Samaturu District and What are the obstacles in the utilization of People's Business Credit (KUR) funds. This study aims to determine whether customers use the funds provided in accordance with the initial agreement to provide credit and what are the obstacles faced by the debtor in managing the People's Business Credit (KUR) fund to develop their business.The research method used includes the type of research in the form of qualitative research, and the objects of this research are the customers of the People's Business Credit (KUR), Mantri and Customer Service. Data collection techniques used were observation, interviews, and documentation.The results showed that the utilization of People's Business Credit (KUR) funds in developing Micro, Small and Medium Enterprises (MSMEs) in Tamboli Village, Samaturu District has been well realized, seen from the level of debtor income before and after taking the increased People's Business Credit (KUR) funds. The obstacles in the utilization of People's Business Credit (KUR) funds in developing Micro, Small and Medium Enterprises (MSMEs) in Tamboli Village, Samaturu District are crop failure and stagnant business.